OMALIZUMAB: CURRENT STATUS IN ASTHMA THERAPY - VIKAS SETH; SHAILESH YADAV (International Journal of Pharma and Bio Sciences, 2015)
Bronchial asthma is characterised by inflammation in airways leading to hyper-reactivity and spasm of the bronchial smooth muscle, oedema and disruption of the mucosa, and obstruction of the lumen by mucus. The drugs used for asthma are broadly classified into bronchodilators (reliever therapies) and anti-inflammatory drugs (preventer therapies). The preventer therapies mainly include corticosteroids besides mast cell stabilizers, antileukotriene drugs and omalizumab. Omalizumab is a humanised monoclonal antibody which binds to circulating IgE. This compound has demonstrated efficacy in the patient population in a number of clinical studies and its use for severe allergic asthma has been endorsed by several international consensus bodies. It is generally indicated for patients unresponsive to high-dose inhaled steroids and have allergy as an important cause of their asthma. Omalizumab is given as a subcutaneous injection every two to four weeks depending on dose which in turn depends on the body weight and the IgE level. This review will further discuss the status of Omalizumab in the management of asthma and where does it fit into the treatment of asthma of different severities.